Variable Antecedents of Employee Performance Election Commission Secretariat East Kalimantan Province - Senjaning Festiyanti; Tetra Hidayati; Siti Maria (Journal of Social Research, 2023)
Building a collaborative government requires different types of leadership styles that build and maintain trust among the various groups and individuals involved. The purpose of this study is to analyze the direct influence of servant leadership on the self-efficacy of employees of the General Election Commission (KPU) Secretariat of East Kalimantan Province. The population in this study is employees of the Secretariat of the General Elections Commission (KPU) of East Kalimantan Province. The sampling technique used in this study is using saturated samples, which is a sampling technique when all members of the population are used as samples. The research instrument used in this study is a structured questionnaire and uses a Likert scale to measure the variables used as research objects. PLS can simultaneously analyze constructs formed with reflective and formative indicators. The purpose of PLS is to assist researchers for prediction purposes. There are two model evaluations in PLS, namely the measurement model (Outer Model), which is a model that measures the indicator with its variables, and the structural model (Inner Model), which is a model that measures between one variable and another.